Synthesis and Refractive Index Characterization of EBBA Liquid Crystal - Mahdi, Soror A; Khorsheed, Suha M; Ahmed, Ahmed K; Salloom, Hussein T (Al-Nahrain Journal of Science, 2018)
In this paper, the Nematic Liquid Crystal (NLC) N-(4'-ethoxybenzylidene)-4-n-butylaniline (EBBA) with transition temperature range between (36-80) ℃ was prepared and identified using Fourier transform infrared spectroscopy (FTIR).The prepared compound (EBBA) was used to calculate the values of refractive index at different temperatures and measurements were done in the temperature range (25-80)℃. The result shows, the values of refractive index values decreases with increase temperature in thermal range.